DEVELOPMENT OF DENTAL HEALTH EDUCATION BOOKLETS AND VIDEOS IN REDUCING DENTAL AND MOUTH CLEANER DEGREES IN V SD CLASSES - Rusmiati Rusmiati; Linda Marlia (Jurnal Bahana Kesehatan Masyarakat (Bahana of Journal Public Health), 2019)
Efforts to improve dental and oral health can be done with preventive and curative measures. Preventive efforts or prevention of dental and oral diseases have top priority. High incidence of dental disease in the community in Pondok Meja area has not been handled optimally. The low level of education supports a lack of awareness of the importance of people's oral and dental health. This background has led to a lack of willingness to treat dental and oral diseases, especially early childhood, both in health centers and other health agencies. The purpose of this study was to determine the development of booklets and dental health education videos in reducing the degree of dental and oral hygiene in Grade V elementary school children. This research is a Quasi experimental research and data collection from primary data obtained from observations of dental and oral hygiene (OHI-S), and dental health behavior and filling out questionnaires. Samples were 80 people. The results of the study have produced booklets and dental and oral health education videos in reducing the degree of dental and oral hygiene in fifth grade elementary school children. From the analysis of booklets and dental health education videos effective in reducing the degree of dental and oral hygiene in children in grade V SD is indicated by a significance value at 0.000 (p <0.05). It is recommended that dental health workers carry out care services to implement dental health education using booklets and videos for fifth grade elementary school children.